1997
DOI: 10.1007/s001340050436
|View full text |Cite
|
Sign up to set email alerts
|

Altering ventilation-perfusion relationships in ventilated patients with acute lung injury

Abstract: IntroductionSince its description by Ashbaugh and Petty in 1967, the acute respiratory distress syndrome (ARDS) has been a major research focus in pulmonary and critical care medicine. However, despite rigorous investigation, it remains a common and vexing problem with a high (albeit possibly decreasing) mortality and no specific therapy. The cornerstone of managing patients with ARDS continues to be meticulous supportive care. Severe hypoxemia is a defining characteristic and is usually treated by high fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
0
6
0
3
Order By: Relevance
“…As early as 1976 it was reported that placing patients with ALI/ARDS in the prone position improves their oxygenation [ 9 - 17 ]. Prone positioning improves secretion drainage from the airways, relieving lung compression by the heart and abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1976 it was reported that placing patients with ALI/ARDS in the prone position improves their oxygenation [ 9 - 17 ]. Prone positioning improves secretion drainage from the airways, relieving lung compression by the heart and abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the prone position is generally thought to be brought about by better recruitment and/or better ventilation/ perfusion matching [9][10][11]. Because improved oxygenation continued after the patient was returned to the supine position, it is conceivable that better recruitment was obtained with the prone position and was maintained with HFOV after the return to the supine position.…”
Section: Discussionmentioning
confidence: 97%
“…Ao melhorar a relação V/Q, houve também redução da fração de shunt (Qs/Qt). As áreas pouco aeradas na região dorsal são recrutadas com pouca ou nenhuma mudança na ventilação na região ventral do pulmão, provocando, assim, maior homogeneidade na relação V/Q (pela diminuição da proporção de áreas com reduzida V/Q) 11,[26][27][28][29][30] . A melhora da distribuição da relação V/Q na posição prona também pode ser comprovada em seres humanos, observando-se o recrutamento de áreas previamente atelectasiadas, mas sem doença 31 .…”
Section: Discussionunclassified
“…Os valores da paO 2 /FiO 2 obtidos nesta pesquisa (27,7% de melhora no grupo total), após 1 hora de colocação em posição prona, não ficam distantes dos encontrados na literatura (44 a 75%) 28,31,36,38,39 . Provavelmente, nossos resultados tenham relação com a população mista estudada (doença pulmonar obstrutiva e restritiva) e também com o tipo de comprometimento pulmonar envolvido.…”
Section: Discussionunclassified